A review of the internal short circuit mechanism in lithium‐ion batteries: Inducement, detection and prevention. (8th June 2021) - Huang, Lili; Liu, Lishuo; Lu, Languang; Feng, Xuning; Han, Xuebing; Li, Weihan; Zhang, Mingxuan; Li, Desheng; Liu, Xiaobin; Sauer, Dirk Uwe; Ouyang, Minggao
Summary: Internal short circuit (ISC) of lithium‐ion battery is one of the most common reasons for thermal runaway, commonly caused by mechanical abuse, electrical abuse and thermal abuse. This study comprehensively summarizes the inducement, detection and prevention of the ISC. Firstly, the fault tree is utilized to analyze the ISC inducement, including the abuse conditions, improper manufacture and design defects. Secondly, the ISC substitute triggering methods (utilizing mechanical deformation from the outside or utilizing controllable components introduced inside) are summarized considering the randomness of ISC, which have high repeatability. Moreover, these methods can be used to investigate the evolution and the hazard boundary of ISC. The ISC severity is determined by the ISC type, ISC location, ISC area, battery state of charge, capacity, material and structure. There are four types of ISC mode, the danger extends ranking is aluminum‐anode > aluminum‐copper > cathode‐copper > cathode‐anode. The ISC evolution is presented based on the upper summary. Then, the ISC detection methods are reviewed: (1) comparing the measured data with the predicted value from the model; (2) detecting whether the battery has self‐discharge; (3) comparing based on the battery inconsistency and (4) other signals. Finally, the prevention strategies are summarized, which can be used to reduce the ISC risk by blocking electron or lithium‐ion channels in the battery cell.